THE RELATIONSHIP OF OBESITY EVENTS WITH THE QUALITY OF LIFE OF SCHOOL - Puti Kulindam Suto (Jurnal EduHealth, 2021)
The incidence of obesity in Indonesia is increasing every year. In 2013 there were 8.8% of children with obesity in Indonesia, and the incidence of obesity in West Sumatra was 7.7%. Obese children tend to have a poor quality of life. The purpose of this study was to examine the relationship between the incidence of obesity and the quality of life of school-age children. This research is a descriptive analytic study with a cross-sectional approach. This research was conducted from February to July 2017. The samples in this study were all 4th and 5th grade students of SDN 30 Kubu Dalam Padang, totaling 110 respondents. Data collection using the Pediatric Quality of Life Inventory (PedsQL) Generic Core questionnaire version 4.0 and observation sheets to determine the classification of Body Mass Index. The prevalence of obesity in school-age children in this study was 11.8%. The prevalence of children who have a good quality of life is 75 respondents (68.2%). Based on data analysis using the chi square test, there is a relationship between the incidence of obesity and the quality of life of school-age children. This is evidenced by the p value